Thiomicrorhabdus marina sp.nov., an obligate chemolithoautotroph isolated from tidal zone sediment, and genome insight into the genus Thiomicrorhabdus - Tan, Xin-Yun; Liu, Xin-Jiang; Li, Zhao; Yu, Fan; Yang, Hui; Du, Zong-Jun; Ye, Meng-Qi (Frontiers in Marine Science, 2023)
The contribution of microbes to the marine sulfur cycle has received considerable attention in recent years. In this study, a new Gram-stain-negative, aerobic sulfur-oxidizing bacterium, designated strain 6S2-11T, was isolated from tidal zone sediment of the coast of Weihai, China. Strain 6S2-11T was an obligate chemolithoautotroph utilizing thiosulfate as the energy source. Physiological and biochemical experiments, phylogenetic analysis, and comparative genomic analysis were done with strain 6S2-11T. According to genomic analysis, strain 6S2-11T owned a complete thiosulfate oxidation pathway and an untypical nitrogen metabolism pathway. Its relatively small genome also has multiple environmental adaptation mechanisms. The DNA G+C content of strain 6S2-11T was 44.1%. Strain 6S2-11T was observed to grow at 20-37°C (optimum, 35°C), pH 6.0-9.5 (optimum, pH 7.5), and 0.5-5% (w/v) NaCl (optimum, 2.5%). The major cellular fatty acids (>10%) of strain 6S2-11T were Summed Feature 8 (C18:1ω7c/C18:1ω6c), C16:0 and Summed Feature 3 (C16:1ω7c/C16:1ω6c). The comparison of 16S rRNA gene sequences indicated that strain 6S2-11T was most closely to Thiomicrorhabdus xiamenensis G2T (96.8%). Based on the results of phylogenetic analysis, the strain 6S2-11T is a novel specie of the genus Thiomicrorhabdus, for which name Thiomicrorhabdus marina sp.nov. is proposed with the type strain 6S2-11T (=MCCC 1H00523T=KCTC 82994T).